Hubungan Kinerja Keuangan dengan Nilai Perusahaan: Peran Corporate Social Responsibility (CSR) dan Good Corporate Governance (GCG) Sebagai Variabel Pemoderasi - Intan Nurjanah (Business, Accounting and Management Journal, 2023)
This research examines the effect of financial performance on firm value with the existence of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) as moderating variables. The samples in this research are companies that have been selected in Kompas Index 100 from 2016-2017. The data in this research are secondary and taken from the company's annual report and the company's official website. The sampling technique used is purposive sampling, and 70 companies were obtained, with a total of 2 years of observation resulting in 140 samples. The data obtained is analyzed using the classic assumption test before testing the hypothesis. Hypothesis testing uses coefficient of determination, F test, and t-test. The results of the research show that financial performance has a positive effect on firm value. CSR and GCG as moderating variables can strengthen financial performance and firm value.